Aquém do masoquismo - Di Pietro, Vilcélia (2011)
This dissertation problematizes the notion of Masochism, opening it up to other meanings beyond its pathological enclosure. We affirm that Sacher-Masoch, as an artist, uses eroticism and sensuality in order to positively transgress a reality that does not satisfy him, thus producing other realities. He uses the contract, law, and humor in order to depersonalize his characters through the composition and shaping of different forms of subjectivity. Sacher-Masoch creates procedures, both in his life and work, whose power dilutes established forms. In order to illustrate the unfolding of Masochism as a creative field, we use Deleuze s theoretical perspective, Sacher- Masoch s biography, and his literary production. Deleuze performs a re-reading of Freudian Masochism and inflects it: he reevaluates the psychological dynamic, brings new understanding to assemblages of desire, and problematizes the complexity of subjective configurations